Characterization of 3D heterocellular spheroids of pancreatic ductal adenocarcinoma for the study of cell interactions in the tumor immune microenvironment - Giustarini, Giulio; Teng, Germaine; Pavesi, Andrea; Adriani, Giulia (Frontiers in Oncology, 2023)
Pancreatic ductal adenocarcinoma (PDAC) is one of the deadliest malignancies nowadays. The available chemo- and immunotherapies are often ineffective in treating PDAC due to its immunosuppressive and highly desmoplastic tumor immune microenvironment (TIME), which is hardly reproduced in the existing preclinical models. The PDAC TIME results from a peculiar spatial organization between different cell types. For this reason, developing new human models recapitulating the tissue organization and cell heterogeneity of PDAC is highly desirable. We developed human 3D heterocellular tumor spheroids of PDAC formed by cancer cells, endothelial cells, pancreatic stellate cells (PSC), and monocytes. As a control, we formed spheroids using immortalized epithelial pancreatic ductal cells (non-cancerous spheroids) with cellular heterogeneity similar to the tumor spheroids. Normal spheroids containing endothelial cells formed a complex 3D endothelial network significantly compromised in tumor spheroids. Monocyte/macrophages within the 4-culture tumor spheroids were characterized by a higher expression of CD163, CD206, PD-L1, and CD40 than those in the non-cancerous spheroids suggesting their differentiation towards an immunosuppressive phenotype. The heterocellular tumor spheroids presented a hypoxic core populated with PSC and monocytes/macrophages. The 4-culture tumor spheroids were characterized by spatial proximity of PSC and monocytes to the endothelial cells and a cytokine signature with increased concentrations of CXCL10, CCL2, and IL-6, which have been observed in PDAC patients and associated with poor survival. Further, 4-culture tumor spheroids decreased the concentrations of T-cell chemoattracting cytokines, i.e., CCL4, CCL5, and CXCL9, when compared with the non-cancerous spheroids, revealing a critical immunosuppressive feature of the different types of cells forming the tumor spheroids. Our results showed that the 4-culture tumor spheroids better resembled some critical features of patients’ PDAC TIME than monoculture tumor spheroids. Using the proposed human 3D spheroid model for therapy testing at the preclinical stage may reveal pitfalls of chemo- and immuno-therapies to help the development of better anti-tumor therapies.